Study on lettuce cultivation substrate based on fungus residue of Auricularia auricula - LIU Lin; GAO Feng; HAN Ning; ZHENG Taiji; WANG Tianlong; ZHOU Peihua; HE Shumin; WANG Jiajia; FU Minjie (浙江大学学报. 农业与生命科学版)
The effects of different volumes and proportions of lettuce cultivation substrates prepared by materials such as fungus residue of Auricularia auricula, vermiculite, perlite and organic fertilizer on the growth and quality of lettuce were compared and explored. The results showed that the water holding capacity of the substrate within fungus residue was more than two times of the control and was significantly improved. The mixture of vermiculite, perlite, organic fertilizer and fungus residue had high contents of available phosphorus, total potassium, total nitrogen and good water retention, which were beneficial to the growth of lettuce. The production indexes such as plant height, number of blades per plant, leaf area per plant, yield and the contents of ascorbic acid, soluble sugar and soluble protein of lettuce treated with some substrates were higher than those cultivated in soil. According to the comprehensive judgment of biological quality, the suitable formulas were V (fungus residue)∶V (organic fertilizer)∶V (vermiculite)=4∶2∶2 (T13), V (fungus residue)∶V (organic fertilizer)∶ V (vermiculite)∶ V (perlite)=4∶2∶1.5∶0.5 (T14), and V (fungus residue)∶V (organic fertilizer)∶V (vermiculite)∶ V (perlite)=5∶2∶1.5∶0.5 (T17). The nitrate content of lettuce was positively correlated with the proportion of organic fertilizer, but negatively correlated with the proportion of fungus residue. With a reasonable and scientific ratio, the cultivation substrate based on fungus residue can replace the traditional cultivation substrate of lettuce, and improve the quality and yield of lettuce.